Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's analyze the given functions and how they relate to each other.
1. The function [tex]\( f(x) = 3^x \)[/tex] is our original function. This is an exponential function with a base of 3.
2. The function [tex]\( g(x) = 3^x - 2 \)[/tex] is derived from [tex]\( f(x) \)[/tex]. We need to determine how this new function [tex]\( g(x) \)[/tex] compares to [tex]\( f(x) \)[/tex].
Looking closely at the equation [tex]\( g(x) = 3^x - 2 \)[/tex]:
- We see that [tex]\( g(x) \)[/tex] is formed by taking the value of [tex]\( f(x) \)[/tex] and subtracting 2.
In transformation terms, subtracting 2 from the entire function [tex]\( f(x) \)[/tex] translates the graph downward along the y-axis. Specifically, every point on the graph of [tex]\( f(x) \)[/tex] is moved 2 units lower to form the graph of [tex]\( g(x) \)[/tex].
Let's break this down step-by-step:
1. Start with the function [tex]\( f(x) = 3^x \)[/tex]. This is the original graph.
2. To form [tex]\( g(x) = 3^x - 2 \)[/tex], you take each y-value of [tex]\( f(x) \)[/tex] and decrease it by 2 units.
3. This results in a vertical shift downward by 2 units. For example:
- If [tex]\( f(1) = 3^1 = 3 \)[/tex], then [tex]\( g(1) = 3^1 - 2 = 3 - 2 = 1 \)[/tex].
- Similarly, if [tex]\( f(2) = 3^2 = 9 \)[/tex], then [tex]\( g(2) = 3^2 - 2 = 9 - 2 = 7 \)[/tex].
Every value of [tex]\( f(x) \)[/tex] is decreased by 2, indicating a vertical shift downward.
Therefore, the correct answer is:
- The graph of [tex]\( g(x) \)[/tex] is a translation of [tex]\( f(x) \)[/tex] 2 units down.
So the correct statement is:
The graph of [tex]\( g(x) = 3^x - 2 \)[/tex] is a translation of [tex]\( f(x) \)[/tex] 2 units down.
1. The function [tex]\( f(x) = 3^x \)[/tex] is our original function. This is an exponential function with a base of 3.
2. The function [tex]\( g(x) = 3^x - 2 \)[/tex] is derived from [tex]\( f(x) \)[/tex]. We need to determine how this new function [tex]\( g(x) \)[/tex] compares to [tex]\( f(x) \)[/tex].
Looking closely at the equation [tex]\( g(x) = 3^x - 2 \)[/tex]:
- We see that [tex]\( g(x) \)[/tex] is formed by taking the value of [tex]\( f(x) \)[/tex] and subtracting 2.
In transformation terms, subtracting 2 from the entire function [tex]\( f(x) \)[/tex] translates the graph downward along the y-axis. Specifically, every point on the graph of [tex]\( f(x) \)[/tex] is moved 2 units lower to form the graph of [tex]\( g(x) \)[/tex].
Let's break this down step-by-step:
1. Start with the function [tex]\( f(x) = 3^x \)[/tex]. This is the original graph.
2. To form [tex]\( g(x) = 3^x - 2 \)[/tex], you take each y-value of [tex]\( f(x) \)[/tex] and decrease it by 2 units.
3. This results in a vertical shift downward by 2 units. For example:
- If [tex]\( f(1) = 3^1 = 3 \)[/tex], then [tex]\( g(1) = 3^1 - 2 = 3 - 2 = 1 \)[/tex].
- Similarly, if [tex]\( f(2) = 3^2 = 9 \)[/tex], then [tex]\( g(2) = 3^2 - 2 = 9 - 2 = 7 \)[/tex].
Every value of [tex]\( f(x) \)[/tex] is decreased by 2, indicating a vertical shift downward.
Therefore, the correct answer is:
- The graph of [tex]\( g(x) \)[/tex] is a translation of [tex]\( f(x) \)[/tex] 2 units down.
So the correct statement is:
The graph of [tex]\( g(x) = 3^x - 2 \)[/tex] is a translation of [tex]\( f(x) \)[/tex] 2 units down.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.